Laparoscopic Reconstructive Surgery is Superior to Vaginal Reconstruction in the Pelvic Organ Prolapse - Park, Young-Han (Ivyspring International Publisher, 2014)
Background: Our purpose was to provide the clinical advantages of the laparoscopic approach compare to the vaginal approach in correcting uterine and vaginal vault prolapse. Methods: Between June 2007 and June 2011, 174 women were admitted to HUMC (Hallym University Medical Center) and underwent pelvic reconstructive surgery for prolapsed vaginal vault and uterus. Upon retrospective review of the medical records, 174 of the patients who had symptoms of pelvic organ prolapsed and Baden-Walker prolapse grade ≥ 2 were selected and divided into two groups as follows: vaginal approach group (n=120) and laparoscopic approach group (n=54). We compared the results of clinical outcome by analyzing Student's t-test and χ(2)-test or the Fisher exact test as appropriate. Results: There were significant difference in success rates without reoperation for recurrence as 91.7% (vaginal approach group, n=110) vs 100% (laparoscopic approach group, n=54), p=0.032. Mean follow-up duration was 31.3 ± 7.6 months for vaginal approach group and 29.7 ± 9.7 months for laparoscopic approach group. The Foley catheter indwelling duration (4.7± 1.9 vs 3.4±2.1 days, p< 0.001) and the length of postoperative hospitalization (6.4 ± 2.1 vs 5.0 ± 1.9 days, p <0.001) were significantly longer in vaginal approach group, whereas the operative time was significantly longer (108.2 ± 38.6 vs 168.3 ± 69.7 minutes, p <0.001) in laparoscopic approach group. Conclusions: Our result suggest there is significantly lower recurrence rate requiring reoperation and less catheterization time but increased operative time for laparascopic sacrocolpopexy.